2011
DOI: 10.1097/01.naj.0000398045.00299.64
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: The Role of the Non-ICU Staff Nurse on a Medical Emergency Team: Perceptions and Understanding

Abstract: bedside nurse, medical emergency team, non-ICU staff nurse, nurse attitudes, patient crisis, patient safety, rapid response system, survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…26 Even receiving criticism from the arriving MET team that the patient was not sufficiently unwell has been cited by nurses as a barrier to activation. 27 …”
Section: Discussionmentioning
confidence: 99%
“…26 Even receiving criticism from the arriving MET team that the patient was not sufficiently unwell has been cited by nurses as a barrier to activation. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Each study developed a new local survey tool to address specific study aims except one, which used a locally modified version of a previously developed tool (Beebe et al., ). Only four referenced other work to inform the development or administration of the instrument (McIntyre et al., ; Pusateri, Prior, & Kiely, ; Rotella, Yu, Ferguson, & Jones, ; Stevens et al., ). While all studies reported that the newly developed surveys had pretesting prior to distribution, none provided any convincing evidence of instrument reliability or validity.…”
Section: Quality Appraisal Of Study Methodsmentioning
confidence: 99%
“…Three studies provided clear justification for sample size calculations (Plowright et al., ; Sarani et al., ; Stevens et al., ), and four described representativeness of the sample (Jones et al., ; Pusateri et al., ; Sarani et al., ; Stevens et al., ), and the population sampling frame (Jones et al., ; Rotella et al., ; Sarani et al., ; Stevens et al., ). Ethics approval was noted in every study, with three exempted as local quality improvement surveys (Plowright et al., ; Salamonson et al., ; Stevens et al., ).…”
Section: Quality Appraisal Of Study Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a RRS suffers from the lack of integration in hospitals. A by the nurses are the discouragement by the doctors, the fear of being subjected to criticism, and the adherence to models that lead to contact the ward doctors before activating the MET system [104,105]. An Italian multicenter survey [106] involved doctors and nurses, in a group of 10 hospitals; findings of the study showed that, for the nurses, the ward doctors were the main obstacle to MET activation.…”
Section: Evaluating the Type Of Interventionmentioning
confidence: 99%